1989
DOI: 10.1111/j.1600-051x.1989.tb01626.x
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole plus amoxycillin in the treatment of Actinobacillus associated periodontitis

Abstract: The potential use of an adjunctive therapy of metronidazole plus amoxycillin for the subgingival elimination of Actinobacillus actinomycetemcomitans in periodontitis patients was investigated. 22 patients participated in this study, 11 with localized juvenile periodontitis (LJP) and 11 with rapidly progressive periodontitis (RPP). 14 patients had received periodontal treatment in the past. All patients were subgingivally infected with A. actinomycetemcomitans. After mechanical subgingival debridement in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
206
1
7

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(226 citation statements)
references
References 20 publications
10
206
1
7
Order By: Relevance
“…However, the results of the pilot are comparable to those of metronidazole in the same human study on the effects of metronidazole plus cefixime and fluids (10), which indicates that the hydroxymetabolite probmetronidazole plus ciprofloxacin indicate that in vitro synably contributes significantly to the effectiveness of the ergy between metronidazole, its hydroxymetabolite, and metronidazole-amoxicillin combination. The nature of the cefixime and ciprofloxacin may have a predictive value for The results of previous studies (5,11,15,18,26,31,32,34,35) and the results of our pilot study suggest that eradication ofA. actinomycetemcomitans is predictable when combinations of antibiotics show in vitro synergism.…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…However, the results of the pilot are comparable to those of metronidazole in the same human study on the effects of metronidazole plus cefixime and fluids (10), which indicates that the hydroxymetabolite probmetronidazole plus ciprofloxacin indicate that in vitro synably contributes significantly to the effectiveness of the ergy between metronidazole, its hydroxymetabolite, and metronidazole-amoxicillin combination. The nature of the cefixime and ciprofloxacin may have a predictive value for The results of previous studies (5,11,15,18,26,31,32,34,35) and the results of our pilot study suggest that eradication ofA. actinomycetemcomitans is predictable when combinations of antibiotics show in vitro synergism.…”
Section: Methodsmentioning
confidence: 52%
“…For adequate treatment of this infection, antibiotics are required. In 1989, van Winkelhoff et al (34) showed that mechanical treatment followed by a regimen of metronidazole and amoxicillin for 7 days is effective in eliminating A. actinomycetemcomitans from the infected sites. Recently, this was confirmed in a large patient group, in which more than 95% eradication of the microorganism was reported (35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selective media were developed that allowed it to be detected even when it was greatly outnumbered by other plaque species (Slots, 1982;Mandell et al, 1987). As a result, it was implicated, on the basis of association-type studies, as a putative periodontal pathogen in refractory periodontitis, early-onset periodontitis, and in the rapidly deteriorating lesion (Tanner et al, 1979;Dzink et al, 1988;van Winkelhoff et al, 1989;Slots et al, 1990a;Haffajee and Socransky, 1994). Its persistence in plaque and presence within the gingival tissue were used to design antimicrobial regimens to eradicate it from both the plaque and the gingiva (Slots and Rosling, 1983;Mandell and Socransky, 1988;Goene et al, 1990;Christersson and Zambon, 1993;van Winkelhoff et al, 1992;Goodson, 1994).…”
Section: (A) the Non-specific Plaque Hypothesismentioning
confidence: 99%
“…Infecties die worden veroorzaakt door exogene pathogenen worden meestal met antibiotica behandeld. Deze weg is ook gevolgd bij de behandeling van ernstige parodontale infecties waarbij deze bacteriën zijn betrokken ( Van Winkelhoff et al, 1989;Winkel et al, 2001). …”
Section: Porphyromonas Gingivalisunclassified